BETTER SELF-FINANCING EFFICIENCIES OF TOP UNIVERSITIES? THE CASE OF NTU IN TAIWAN: Received: 28th November 2025, Revised: 02nd December 2025, Accepted: 05th December 2025, Date of Publication: 12th December 2025 - Chiou Rung Chen, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Utilizing Data Envelopment Analysis (DEA) in conjunction with financial data analysis, this study assessed the self-financing efficiencies of the top university National Taiwan University (NTU) from 2012 to 2023. The results underscored the infeasibility of the current financial autonomy model for public universities in Taiwan, amidst the simultaneous and rapid exacerbation of the declining birth rate and the widening social wealth disparity. Furthermore, the findings signaled a precarious threat to the financial stability and long-term sustainability of public universities in Taiwan under the existing system. This suggested an urgent need for policy reforms to ensure the financial sustainability of universities and enable them to fulfill their social responsibilities.